Life cycle assessment of a ceramic glaze containing copper slags and its application on ceramic tile. Issue 1 (4th October 2019) - Mohaddes Khorassani, Sara; Siligardi, Cristina; Mugoni, Consuelo; Pini, Martina; Cappucci, Grazia Maria; Ferrari, Anna Maria
Abstract: Even though copper slags have many possible applications, their disposal is still practiced, creating long‐term waste management problems. This led to the investigation of new products for residential applications, taking advantages of the interesting chemical properties of copper slag. This study aims to assess the environmental impact of the use of copper slag as secondary raw material in a ceramic glaze composition and to compare it with a traditional glaze. A manufacturing process was designed, through an industrial scale up operation from experimental laboratory data and the entire life cycle of the products was analyzed using the Life‐cycle assessment (LCA) methodology. Considering the production of a ceramic glaze containing copper slag, the most impacting process resulted the one related to frit production, due to the large amount of thermal energy necessary for the raw materials melting. The comparative LCA analysis carried out between the frit obtained from metallurgical slags and a traditional one, demonstrated that the innovative ceramic frit has a greater environmental advantage. The LCA analysis allowed to highlight the most impactful stages of an industrial process using copper slag as a secondary raw material for glaze production and to quantify the potential environmental advantages of this operation.